Pengaruh Sistem Informasi Akuntansi, Program Pelatihan, Dukungan Manajemen Puncak Dan Insentif Terhadap Kinerja Karyawan - Ni Nyoman Ayu Sariningsih; Sang Ayu Putu Arie Indraswarawati (Hita Akuntansi dan Keuangan, 2022)
A pharmaceutical company is a commercial business company that focuses on researching, developing and distributing drugs, especially in healthcare. The success and survival of a company can be seen from the performance possessed by employees. The Covid-19 pandemic has caused changes in the work system and restrictions on activities in accordance with health protocols. This affects the pace of economic growth in the health sector which is a challenge for pharmaceutical companies to survive during this pandemic. This study aims to examine the effect of accounting information systems, training programs, top management support, and incentives on employee performance in pharmaceutical companies in Denpasar City. This research is in the form of an associative using questionnaires on 79 respondents who are medical representatives, namely salespeople in pharmaceutical companies who specifically market pharmaceutical products to doctors' practices or to hospitals. The method of determining the sample in this study used the Slovin technique and the data analysis technique used was multiple linear regression analysis. The results showed that accounting information systems, training programs, top management support, and incentives have a positive and significant impact on employee performance.